PENGARUH AKUNTABILITAS, SISTEM PENGENDALIAN INTERN, DAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA ORGANISASI PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA SURABAYA - Siti Nur Azizah; Muhammad Taufiq Hidayat (Journal of Student Research, 2023)
Every organization in a government agency has a mission to achieve. Achievement of goals and objectives that have been set through a performance accountability system which is a general indicator for measuring mission achievement. This research aims to adhere to accountability, internal control siste and accounting information siste on organizational performance in government agencies. This study used a quantitative method with primary data obtained from respondents through questionnaires distributed to employees of the Regional Financial and Asset Management Agency located in the City of Surabaya. The data analysis technique used is progra SPSS version 20. The results of this study show that accountability has a significant positive effect on organizational performance, the internal control system has no positive and significant effect on organizational performance, the accounting information system has a positive and significant effect on organizational performance and accountability, the internal control system and the accounting information system together have a significant positsive effect on organizational performance.